Avatime noun classes and concord - Russell G. Schuh (LibraryPress@UF, 1995)
Avatime is one of 14 "Central-Togo" (or "Togo Remnant") languages, spoken in Ghana, Togo, and Benin. These languages differ from their nearest Kwa group relatives in that they have active systems of noun classes and concord. Avatime has 13 noun classes, each with a distinct nominal prefix. Prefixes (as well as most other affixes) agree in [ATR] vowel harmony with the host noun root. Some classes impose invariable low tone on the prefix while prefix tone of other classes may be any of three lexically determined tones. Definiteness is marked by a set of suffixes. The ultimate segmental shapes and tones of these suffixes depend on the interaction of the respective class prefix shapes and coalescence phenomena with stem final vowels. There are correlations between noun class and nominal semantics, and nominal derivation is done in part through class choice. A number of attributive modifiers show class concord with the head noun. In the variety of Avatime studied here, such concord is only though vocalic prefixes on attributive modifiers, not by full CV prefixes as is typical of Bantu languages. Some attributives also have "tonal concord", which is not class concord per se, but refers to the tone of the head noun's prefix. Not all attributive modifiers have overt concord marking.